2020
DOI: 10.1186/s12974-020-01973-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting HMGB1-RAGE axis prevents pro-inflammatory macrophages/microglia polarization and affords neuroprotection after spinal cord injury

Abstract: Background Spinal cord injury (SCI) favors a persistent pro-inflammatory macrophages/microglia-mediated response with only a transient appearance of anti-inflammatory phenotype of immune cells. However, the mechanisms controlling this special sterile inflammation after SCI are still not fully elucidated. It is known that damage-associated molecular patterns (DAMPs) released from necrotic cells after injury can trigger severe inflammation. High mobility group box 1(HMGB1), a ubiquitously express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(95 citation statements)
references
References 66 publications
0
82
0
1
Order By: Relevance
“…Furthermore, the disintegration of astrocytes, detected by the GFAP upregulation, can stimulate the overexpression of other inflammatory mediators involved in neurological damage. Necroptotic astrocytes release the HMGB1 protein and stimulate the HMGB1-RAGE axis [47] , [48] that can induce inflammatory events leading to organ dysfunctions, including the brain. The binding of HMGB1 to RAGE promotes the transcription of inflammatory factors including the NFκB and MAPK pathways [49] , and its sustained activation causes cell death by stimulating the production of reactive oxygen species [50] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the disintegration of astrocytes, detected by the GFAP upregulation, can stimulate the overexpression of other inflammatory mediators involved in neurological damage. Necroptotic astrocytes release the HMGB1 protein and stimulate the HMGB1-RAGE axis [47] , [48] that can induce inflammatory events leading to organ dysfunctions, including the brain. The binding of HMGB1 to RAGE promotes the transcription of inflammatory factors including the NFκB and MAPK pathways [49] , and its sustained activation causes cell death by stimulating the production of reactive oxygen species [50] .…”
Section: Discussionmentioning
confidence: 99%
“…In all of the cells mentioned, and additionally, in the endothelial and other vascular cells, the activation of NADPH oxidases (Nox) [ 92 ] leads to enhanced ROS formation, which also stimulates inflammatory responses inasmuch as other causes of oxidative stress do. Independently of cell type, any dying cell can release proinflammatory DAMP factors (damage-associated molecular pattern), such as histone H1 [ 93 ] or HMBG1 (high-mobility group box 1) [ 94 , 95 , 96 ]. Both of them activate microglia, and the suppression of HMBG1 can reduce ROS formation and proinflammatory cytokine release.…”
Section: Melatonin Influences Glial and Glial-neuronal Interactionsmentioning
confidence: 99%
“…Neutralizing HMGB1 with anti-HMGB1 antibody and reduced HMGB1 in the conditioned medium results in decreased M2 polarization of macrophages. RAGE exists on the membrane of macrophages and is the surface receptor of HMGB1, which can bind by HMGB1 to regulate macrophage polarization [34,35]. In this study, we found that anti-REAG can prevent M2 polarization of macrophages which induced by HMGB1.…”
Section: Discussionmentioning
confidence: 51%